The Congressional experience in Chile (1828-2022): an atypical case in Latin America - Arellano, Juan Carlos; De Camargo Lima, Rodolfo; Cuevas, Rodrigo (Estudios Internacionales, 2024)
This paper investigates parliamentary experiences and compares legislatures in the Congress of Chile from 1828 to 2022, considering the uniqueness of Chile as an outlier case compared to Latin America. We collected original data from all congress members and senators using Chile’s National Congress Library bibliographical data. Using a data analysis, we combined quantitative descriptive analysis and qualitative historical case studies. Initially, we quantitatively described the experiences across different historical constitutions and legislative career tracks. Afterward, we divided three groups of legislatures for case studies, each with varying experience levels: high, average, and low. We examined and compared these groups through a qualitative and historical approach to identify patterns in their relationship with the executive branch. The case studies revealed that less experienced legislatures tend to adopt a more challenging and less collaborative standpoint toward the executive. In contrast, more experienced ones suggested having their own agendas and challenged the government more. Finally, legislatures with average experience appear more cooperative and have implemented significant political reforms. We conclude that parliamentary experience matters for the legislative-executive relationship.